2014
DOI: 10.3390/ijms150813802
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammation-Related Gene S100A12 Is Positively Regulated by C/EBPβ and AP-1 in Pigs

Abstract: S100A12 is involved in the inflammatory response and is considered an important marker for many inflammatory diseases in humans. Our previous studies indicated that the S100A12 gene was abundant in the immune tissues of pigs and was significantly upregulated during infection with Haemophilus parasuis (HPS) or porcine circovirus type 2 (PCV2). In this study, the mechanism of transcriptional regulation of S100A12 was investigated in pigs. Our results showed that S100A12, CCAAT/enhancer-binding protein beta (C/EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Statins are believed to also exert pleiotropic lipid-lowering-independent effects, including antiinflammatory effects, which are regulated by various distinct mechanisms via HMG-CoA reductasedependent/independent pathways 30) . Although the precise regulatory mechanism of S100A12 expression remains unclear, several feasible mechanisms were recently reported 31,32) . Based on the findings of these studies, S100A12 expression was transcriptionally up-regulated by CCAAT/enhancer-binding protein and activator protein.…”
Section: Discussionmentioning
confidence: 99%
“…Statins are believed to also exert pleiotropic lipid-lowering-independent effects, including antiinflammatory effects, which are regulated by various distinct mechanisms via HMG-CoA reductasedependent/independent pathways 30) . Although the precise regulatory mechanism of S100A12 expression remains unclear, several feasible mechanisms were recently reported 31,32) . Based on the findings of these studies, S100A12 expression was transcriptionally up-regulated by CCAAT/enhancer-binding protein and activator protein.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the S100A12 gene in the spleen of diseased pigs infected with Haemophilus parasuis ( H. parasuis ) was upregulated 16.6 times, but this was not observed in healthy pigs. In the follow‐up experiment, they also found that this gene is cooperatively and positively regulated by CCAAT/enhancer‐binding protein beta (C/EBPβ) and activator protein‐1 (AP‐1) in pigs [80, 81]. Since S100A8, S100A9 and S100A12 have similar functions, these genes are located on pig chromosome 4 and closely linked to SW512 .…”
Section: The Protein Levels Of S100a8 S100a9 and S100a12 Are Closely ...mentioning
confidence: 99%
“…The transcription activation of S100A12 was positively regulated by C/EBPβ (CCAAT/enhancerbinding protein beta) and activator protein-1 (AP-1) and further participated in the regulation of immune response in pigs. The same regulatory effect may occur in S100A8 and S100A9 to a greater extent because they share a similar expression pattern to the S100A12 gene and have C/EBPβ and AP-1 binding sites in their promoter regions [14,16]. The expression of S100A8, S100A9, and S100A12 are also dramatically induced in porcine whole-blood cultures by both lipopolysaccharide (LPS) and polyinosinic-polycytidylic acid (poly (I: C)) and with porcine circovirus type 2 (PCV-2) infection in vivo [14,15].…”
Section: Introductionmentioning
confidence: 99%